In Vivo Anchoring Bis‐Pyrene Probe for Molecular Imaging of Early Gastric Cancer by Endoscopic Techniques. Issue 4 (27th November 2022) - Luo, Qiang; Fan, Chaoqiang; Ying, Wang; Peng, Xue; Hu, Yiyang; Luan, Zhaohui; Ye, Shaosong; Gong, Chunli; Huang, Yu; Xiao, Yufeng; Chen, Yang; Xing, Malcolm; et al.
Abstract: With the development of blue laser endoscopy (BLE) technique, it's often used to diagnose early gastric cancer (EGC) by the morphological changes of blood vessels through BLE. However, EGC is still not obvious to identify, resulting in a high rate of missed diagnosis. Molecular imaging can show the changes in early tumors at molecular level, which provides a possibility for diagnosing EGC. Therefore, developing a probe that visually monitors blood vessels of EGC under BLE is particularly necessary. Herein, a bis‐pyrene (BP) based nanoprobe (BP‐FFVLK‐(PEG)‐RGD, M1 ) is designed, which can target angiogenesis and self‐assemble into fibers in situ, resulting in stable and long‐term retention in tumor. Moreover, M1 probe can emit yellow‐green fluorescence for imaging under BLE. M1 probe is confirmed to steadily remain in tumor for up to 96 hours in mice transplanted subcutaneously. In addition, the M1 probe is able to target angiogenesis for molecular imaging of isolated human gastric cancer tissue under BLE. Finally, M1 probe i.v. injected into primary gastric cancer model rabbits successfully highlighted the tumor site under BLE, which is confirmed by pathological analysis. It's the first time to develop a probe for diagnosing EGC by visualizing angiogenesis under BLE, showing great clinical significance. Abstract : An M1 probe is designed for diagnosing early gastric cancer (EGC) through visualizing angiogenesis under blue laser endoscopy (BLE). M1 probe can remain in tumor for up to 96 h in mice transplanted subcutaneously. Moreover, the M1 probe is confirmed to target angiogenesis for molecular imaging of isolated human gastric cancer tissue and primary gastric cancer model rabbits under BLE.